Cancer Pain Management in French-Speaking African Countries : Assessment of the Current Situation and Research into Factors Limiting Treatment and Access to Analgesic Drugs - (:unkn) unknown (My University, 2024)
Pain management is an urgent, unmet need. The International Association for the Study of Pain argues that pain is a public health issue as it is pervasive, disabling yet under-treated and very often under-diagnosed. It is estimated that 20% of adults experience moderate-to-severe pain, with pain being the leading cause of long-term disability. In addition, it is estimated that only 7.5% of people globally have access to adequate opioid analgesics when in need. Similarly, Zin notes that 92% of opioids globally are consumed by 17% of population. This is despite the fact that up to 2016, the use of opioids doubled every 10 years. This is a stark division of resources, often displayed as harmful overuse of opioid analgesics in some countries and harmful underuse in others.The inequities of pain treatment are well documented. The main causes of these inequities are lack of education, diverse access to treatments, and disproportionate use of pain treatments. Therefore, while pain treatment protocols may be developed, the underlying barriers to care must be addressed. Specifically, there is a lack of access to analgesics, but especially opioids, an essential medicine, in low- and middle-income countries.In many African countries, cancer incidence is increasing, and pain with it. Yet, access to certain treatment options such as opioid analgesics is severely restricted. Cleary et al. note that from their research on 25 of the 52 African countries “all of the surveyed countries in Africa have <10% of the anticipated Adequacy of Consumption Measure (ACM) for opioids”.The paucity of research on pain treatment in Africa is significant, and especially French-speaking Africa. The burden of disease, specific focus on cancer pain and the barriers to treatment in this context is under-researched. Significantly, this will continue to impact access to treatment, the development of policy and regulation to provide comprehensive care, and as disease burdens incre
Keywords: African Research